On certain distance and degree based topological indices of Zeolite LTA frameworks. (4th May 2020) - Prabhu, S; Murugan, G; Cary, Michael; Arulperumjothi, M; Liu, Jia-Bao
Abstract: Zeolites are aluminosilicates with extensive application both commercially and in materials science. Current applications include dehydrating natural gas and in humidity sensors. Synthesis of new frameworks is an important area of research in chemistry and materials science. The Zeolite LTA framework in particular is getting much attention in this area due to its potential for application. Topological indices are graph invariants which provide information on the structure of graphs and have proven very useful in quantitative structure activity relationships (QSAR) and quantitative structure property relationships (QSPR) at predicting important chemico-phyiscal aspects of chemical compounds. In this paper we compute nine of the most significant distance based topological indices of the Zeolite LTA framework and thirteen valency based molecular descriptors.